Active Listening. - Hoppe, Michael H. (Center for Creative Leadership, 2018)
Listening well is an essential component of good leadership. You can become a more effective listener and leader by learning the skills of active listening. Working relationships become more solid, based on trust, respect, and honesty. Active listening is a critical component of the tasks facing today's leaders.